The impact mechanism of teacher positive leadership on study engagement: A visual analysis based on knowledge mapping - zhiyuan, Yang; Anuar, Aimi Binti (International Journal of Innovative Research and Scientific Studies, 2025)
To address the critical issue of insufficient student engagement in higher education, this study maps the intellectual landscape of how "Teacher Positive Leadership," a proactive evolution from "teacher support" empowers students. Using a scientometric approach, we conducted a visual analysis with CiteSpace on 243 core articles from the Web of Science (2005–2025). The analysis identified research hotspots, foundational theories, and emerging frontiers. Results show that research in this domain centers on a core pathway: "teacher leadership → student psychological mechanisms (e.g., self-efficacy, motivation) → study engagement/achievement," with achievement goal theory and study engagement theory as its primary theoretical foundations. A dynamic trend was also identified, showing a research evolution from focusing on academic outcomes to a deeper concern for students’ psychological processes and well-being. We conclude that the shift to a "teacher positive leadership" framework is a necessary evolution in educational research and highlight a promising future direction: developing integrated models that explore multiple psychological mechanisms, such as psychological capital and achievement goals, in diverse cultural contexts.